FORMULATIONS AND EVALUATION OF FILM COATED IMMEDIATE RELEASE TABLETS OF PIRACETAM - Jain, Anshul; Gupta, Dr. Manish Kumar; Sharma, Vijay (Journal of Biomedical and Pharmaceutical Research, 2018)
An immediate release dosage form allows a manufacturer to extend market exclusivity, 100 mg of Piracetam was accurately weighed and transferred to previously dried 100 ml volumetric flask. Drug was dissolved in 0.01N sodium hydroxide solution. The solution was suitably diluted and scanned in the range of 230-380 nm using 0.01N sodium hydroxide solution as blank. The main objective of present work is to formulate safe and bioequivalent film coated immediate release tablet for treatment of cognitive and memory disorder. immediate release Piracetam tablets were prepared by Wet Granulation & Direct Compression. Coating by Ethyl cellulose and Dibutyl sebacate were dissolved in PEG-6000, HPMC-6cps, talc and titanium di oxide were dissolved in water, Both the solution were mixed together and stirred for 45 min to get a homogenous solution. Ten tablets were powdered in a mortar and powder equivalent to 5 mg of Piracetam was taken and extracted with 25 ml of 0.01N Sodium Hydroxide solution by shaking for 15 min. It was filtered and diluted to 50 ml with water. The scaled up formulations B10 and B11 were subjected to accelerated stability studies and parameters like hardness, disintegration time, drug content and in vitro drug release were analyzed after storing them at 40±20C / 75±5% RH for 2 months. Keywords: Tablets, immediate release, Wet granulation, Dry granulation.